Role of intraoperative entroscopy in obscure small bowel gastrointestinal bleed - M. K. Ganesh; Sudheer Kanchodu; Sagar Nambiar Janardhan; H. T. Nagarjun Rao (Wolters Kluwer Medknow Publications, 2024)
Obscure gastrointestinal bleed (OGIB) is defined as bleeding of unknown origin that persists or recurs after a negative initial or primary endoscopy (colonoscopy and upper gastrointestinal [GI] endoscopy) and imaging. Approximately 5% of all GI bleeding is obscure GI bleed. Abnormal blood vessels arteriovenous malformations (AVMs) cause 30%-40% of small intestinal bleeds. AVMs are the main source of bleeding in patients over the age of 50 years. Tumors (benign and malignant), polyps, Crohn's disease, and ulcers are some of the other causes of bleeding. Various diagnostic modalities available to detect small intestinal bleed are upper GI endoscopy, colonoscopy, contrast-enhanced computed tomography scan of the abdomen with angiogram, small bowel enteroscopy, video capsule endoscopy, and scintigraphy studies. Advanced imaging/diagnostic modalities may not be available in all centers, posing a great challenge in the localization of the source of GI bleed. This series highlights the role of diagnostic laparoscopy with intraoperative enteroscope (IOE) in the management of OGIB.